Đáp án:+Giải thích các bước giải:
Bài 1:
a) 3x^2 - 6x
= 3x(x - 2)
v) x^2 - 2x + 1 - y^2
= (x^2 - 2x + 1) - y^2
= (x - 1)^2 - y^2
= (x - 1 - y)(x - 1 + y)
c) 9x^3 - 9x^2y - 4x + 4y
= (9x^3 - 9x^2y) - (4x - 4y)
= 9x^2(x - y) - 4(x - y)
= (x - y)(9x^2 - 4)
= (x - y)(3x - 2)(3x + 2)
d) x^2 - 2x^2 - 8x
= -x^2 - 8x
= -x(x + 8)
Bài 2 :
a) x(x - 1) - x^2 + 2x = 5
=> x^2 - x - x^2 + 2x = 5
=> x = 5
b) 4x^2 - 36x = 0
=> 4x(x - 9) = 0
=> x = 0 hoặc x = 9
c) 2x^2 - 2x = (x - 1)^2
=> 2x^2 - 2x - x^2 + 2x - 1 = 0
=> x^2 - 1 = 0
=> (x- 1)(x + 1) = 0
=> x = 1 hoặc x = -1
d) (x - 7)(x^2 - 9x + 20)(x - 2) = 72
<=> (x^2 - 9x + 14)(x^2 - 9x + 20) = 72
Đặt a = x^2 - 9x + 14
=> a(a + 6) = 72
=> a^2 + 6a - 72 = 0
=> a^2 + 6a + 9 - 81 = 0
=> (a + 3)^2 - 9^2 = 0
=> (a - 6)(a + 12) = 0
@ TH1 : a = 6 => x^2 - 9x + 14 = 6
=> x^2 - 9x + 8 = 0
=> (x - 8)(x - 1) = 0
=> x = 8 hoặc x = 1
@ TH2 : a = -12 => x^2 - 9x + 14 = -12
=> x^2 - 9x + 26 = 0
=> x^2 -9x + 81/4 + 23/4 = 0
=> (x - 9/2)^2 = -23/4 (vô lý)